THE CONCEPT OF TA’DIB IN ISLAMIC EDUCATION AS A SOLUTION TO THE DIGITAL ETHICS CRISIS AMONG STUDENTS: THE PERSPECTIVE OF SYED MUHAMMAD NAQUIB AL-ATTAS - Suyono; Diky Ardha Sundawa; Rizaldi Isnanta; Jailani; Bahtiar Siregar (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The increasingly pervasive development of digital technology has not been fully accompanied by the strengthening of ethical awareness in its practical use. This situation is reflected in various phenomena among students, including the tendency toward excessive use of social media, the declining quality of ethics in online communication, and the weakening of mutual respect in digital spaces. These conditions indicate that digital ethics cannot be understood merely as a technological problem but are closely related to the direction of values and the fundamental goals of education. Departing from this reality, this study aims to examine the concept of ta’dib in the thought of Syed Muhammad Naquib al-Attas as an alternative conceptual framework for responding to the digital ethics crisis from the perspective of Islamic education. This study employs a qualitative approach through library research by critically examining al-Attas’s major works as well as national and international scholarly journal articles from the past five years relevant to digital ethics and Islamic education. The findings reveal that the weakening of digital ethics is rooted in an educational paradigm that tends to emphasize cognitive aspects and technical skill mastery, while the formation of adab as the core of education is neglected. Within this framework, the concept of ta’dib offers a holistic philosophical foundation by positioning education as a process of internalizing adab that integrates intellectual, moral, and spiritual dimensions in an integral manner. Therefore, this study concludes that the application of the concept of ta’dib has the potential to serve as a strategic foundation for building sustainable, value-oriented digital ethics among students that are relevant to the challenges of Islamic education in the digital era.